Employed but Still Unhappy? On the Relevance of the Social Work Norm - Adrian Chadi (Deutsches Institut für Wirtschaftsforschung (DIW), 2011)
In the modern welfare state, people who cannot make a living usually receive financial assistance from public funds. Accordingly, the so-called social work norm against living off other people is violated, which may be the reason why the unemployed are so unhappy. If so, however, labour market concepts based on the notion of promoting low-paid jobs that are subsidised if necessary with additional payments would appear far less favourable. It could be that people are employed, but still unhappy. Using German panel data, this paper examines the relevance of the social work norm and finds a significant disutility effect of living off public funds. Although this is true for employed people as well, the results show that the individual is generally better off having a job that requires additional assistance, than having no job at all. On the other hand, such policies as the recent German labour market reforms can trigger undesired side-effects, if policy-makers ignore the issue of the social work norm.
Keywords: I31; J38; J60; 330; Unemployment; Social benefits; Low-wages; Labour market policies; Social norms; Well-being; Erwerbstätigkeit; Armut; Niedriglohn; Arbeitsmarktreform; Arbeitsethik; Soziale Norm; Zufriedenheit; Deutschland